The Relationship Between Arm Muscle Strength And The Ability To Hit A Kasti Ball Of Class V Students Of Inpres Primary School, Skow Mabo Village, Muaratami District, Ta. 2023/2024 - Tampi, Siane Maria; Marsuki, Marsuki; Wanimbo, Destin (Jurnal Pendidikan Jasmani (JPJ), 2025)
Physical education is part of the general education program which contributes to the overall growth and development of children. Physical education is one of the learning subjects in the elementary school curriculum. Physical education lessons are provided covering various sports and games. One of the small ball sports is the game of rounders. The game of baseball emphasizes excitement and dexterity. The game of rounders is a team sport played by 2 teams and rounders must master the basic techniques of the game, and be in good physical condition including strength, speed, endurance, explosive power, flexibility, balance, coordination, agility, accuracy and good reactions. The game of rounders is one of the games that is really liked by the children of Impres Elementary School, Skow Mabo Village, although sometimes problems often occur because they get into trouble on the field, namely throwing the ball from the field guard because the ball hitter is not fast or not far from the place where he hits the ball, in the end it is replaced. game happens. The aim of this research was to determine whether there was a relationship between arm muscle strength and the ability to hit a baseball in class V of Impres Elementary School, Skow Mabo Village, Muaratami District. The type of research used in this research is correlational research. The method used in this research is a survey method with data collection techniques in the form of tests and measurements.